Cytotoxic and Antibacterial Preussomerins from the Mangrove Endophytic Fungus Lasiodiplodia theobromae ZJ-HQ1 - Chen, Senhua; Chen, Dongni; Cai, Runlin; Cui, Hui; Long, Yuhua; Lu, Yongjun; Li, Chunyuan; She, Zhigang (Journal of natural products (Washington, D.C.), 2016)
Two new chlorinated preussomerins, chloropreussomerins A and B (1 and 2), together with nine known preussomerin analogues, 3–11, were obtained from the endophytic fungus Lasiodiplodia theobromae ZJ-HQ1. Their structures were elucidated by a combination of spectroscopic analyses. The absolute configurations of 1 and 2 were both determined by single-crystal X-ray diffraction using Cu Kα radiation. Chloropreussomerins A and B (1 and 2) are the first chlorinated compounds in the preussomerin family, and preussomerin M (3) is reported for the first time as a natural product. Compounds 1 and 2 showed potent in vitro cytotoxicity against A549 and MCF-7 human cancer cell lines, with IC50 values ranging from 5.9 to 8.9 μM, and compounds 4–7 exhibited significant bioactivity against A549, HepG2, and MCF-7 human cancer cell lines, with IC50 values of 2.5–9.4 μM. In the antibacterial assay, compounds 1, 2, 5–7, and 11 exhibited significant activities against Staphylococcus aureus, with MIC values between 1.6 and 13 μg/mL.